Patrick Geddes's intellectual origins - Macdonald, Murdo (Edinburgh University Press Ltd, 2020)
This book situates Patrick Geddes within his own intellectual background (described by George Davie as 'the democratic intellect') and explores the relevance of that background to Geddes's substantial national and international achievements across a truly impressive range of disciplines.